Fungal Endophthalmitis: Clinical Characteristics, Pathogens, and Factors Affecting Visual Outcome - Xiaoxia Li; Zhi Chen; Xiuwen Zhang; Zimei Zhou; Maureen Boost; Taomin Huang; Xingtao Zhou (MDPI AG, 2024)
Aims: The aims of this study are to investigate the etiology, microbiological spectrum, and risk factors associated with visual outcomes of fungal endophthalmitis (FE) in a tertiary eye specialty hospital in Shanghai, China. Methods: This was a retrospective, single-center case series. The clinical characteristics, etiology, microbiological spectrum, and management, as well as the visual outcomes, were analyzed. Logistic regression was used to analyze the factors related to visual outcomes. Results: This study involved 102 eyes of 92 patients with FE, including 63 males (66.3%). The mean age was 44.4 ± 19.8 years. The most common etiology of FE was trauma (56.5%). The predominant fungal species isolated were Aspergillus spp. (31/93, 33.3%). Pars plana vitrectomy (PPV) and intravitreal antifungal agents was performed initially in 86 (84.3%) and 83 (81.4%) eyes, respectively. Only 35 (34.3%) eyes achieved final best corrected visual acuity (BCVA) of 20/400 or better. Ten (9.8%) eyes had a final BCVA of light perception or worse, and five (4.9%) had to be enucleated. The factors determining better visual outcomes included initial visual acuity better than finger-counting (FC) (odds ratio (OR) 5.811, p = 0.036), the absence of corneal infiltrate (OR 10.131, p = 0.002), and Candida species infection (OR 6.325, p = 0.011). Conclusions: Early diagnosis of FE and a timely vitrectomy, combined with an intravitreal injection of an antifungal drug, can mitigate the devastating results of intraocular fungal infection. Not being infected by Aspergillus spp., an initial BCVA that was no worse than FC, and the absence of corneal involvement were related to better visual prognosis.